Difficulties and reasonable adjustments carried out by Spanish faculty members to include students with disabilities. (22nd September 2019) - Moriña, Anabel; Perera, Víctor H.; Melero, Noelia
Abstract : This study focuses on the experience of 20 Spanish faculty members who teach students with disabilities. We conducted semi‐structured individual and group interviews, and analysed the data using an inductive system of categories and codes. The results of this work describe the difficulties that faculty members encountered when including students with disabilities, and how they attended, through reasonable adjustments, to the educational needs of their students. Their testimonies produced a profile of professionals who recognise their own shortcomings while valuing the actions that they have undertaken in order to meet the needs of their students. From their perspective, these actions were more closely linked to their own willingness and the students' efforts than to the training they had received on disability. In this sense, the present study shows that universities must provide more meaningful training in the field of disability and make firm institutional commitments to supporting their faculty members.